Dilauryl thiodipropionate as a regeneration agent for reclaimed asphalts. (15th February 2023) - Camargo, Ingrid; Hofko, Bernhard; Graziani, Andrea; Grilli, Vittoria
Graphical abstract: Highlights: Study about the feasibility of DLTDP as a regeneration agent for RAP binders. The continuous PG of RAP binders was partially restored due to DLTDP addition. The aging resistance was improved by adding DLTDP into RAP binders. The addition of DLTDP improved the moisture damage resistance of RAP binders. Abstract: Constructing asphalt pavements using reclaimed asphalt pavement (RAP) instead of exclusively virgin materials can significantly reduce environmental impacts and costs. However, the adverse effect of the aged RAP binder on asphalt mixtures' workability and pavements' performance restricts the percentage of RAP added to asphalt mixtures. As a solution, regeneration agents can be used to restore (even if partially) the physical, rheological, and chemical properties lost during the aging of the pavement in the field. Therefore, this paper evaluates the feasibility of using Dilauryl thiodipropionate (DLTDP) as a regeneration agent for RAP binders. This study considered two RAP binders (artificial and field). The impact of the DLTDP on the continuous performance grade of each RAP binder was investigated using the Dynamic Shear Rheometer (DSR). The antioxidant and regenerative effects of DLTDP on RAP binders were assessed by Fourier Transform Infrared spectroscopy (FTIR) and SARA fractionation. The adhesion between each RAP binder and granite aggregate (at dry and wet conditions) was evaluated using the bitumen bond strength (BBS) test. The rheological results indicated the softening effect of DLTDP on RAP binders. This softening effect may be explained by the increase of the maltene fractions (resins) and the reduction of the asphaltene fraction. Additionally, regenerated binders showed better oxidative aging and moisture susceptibility resistance than non-regenerated binders. Overall, the results indicated that adding DLTDP to RAP binders partially restored RAP binders' rheological and chemical composition to the target neat asphalt binder without significantly compromising the adhesion properties and rutting resistance. Moreover, the mentioned results verified the great potential of using DLTDP as a regeneration agent for RAP binders, making it possible to produce good-performing asphalt mixtures with a high RAP percentage.